PENGARUH LATIHAN INTERVAL TRAINING MENGUNAKAN LATIHAN CEPAT DENGAN JARAK PENDEK TERHADAP DAYA TAHAN ANAEROBIK TIM FUTSAL SMK AL-HUDA PEKANBARU - Septian ilham; Ramadi '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem in this research is the endurance of futsal team of SMK Al-Huda Pekanbaru is still lacking, when attending the game between high school as Pekanbaru in GOR Gelanggang Remaja futsal team experienced defeat. This is allegedly because the players of this team experienced a very significant fatigue. This research was conducted in futsal team of SMK Al-Huda Pekanbaru. Population in this research is futsal team of SMK Al-Huda Pekanbaru futsal team of SMK Al-Huda Pekanbaru amounted 10 person. Exercises in this study were tarining intervals using quick exercise with short distances. This type of research is an experiment to see the effect of the form of exercise. The sampling technique uses total sampling, where the total population is sampled. The data retrieval technique is obtained from pree-test and post test. The research instrument used a 300 meter test. The analysis was performed using the t-test. Based on data analysis and discussion, proven with Thitung of 9.63 and Ttabel 1.812. Means Thitung> Tables. At ɑ = 0,05 level. So it can be concluded that there is the effect of training interval training using quick exercise with short distance (X) on anaerobic resistance (Y) on the team of Futsal SMK Al-Huda Pekanbaru.Keywords: Interval training, back and forth running exercises.